A Comparative Study of Teachers’ Decision Making Styles and Their Job Satisfaction in Four Selected Migrant High Schools in Mae Sot District, Tak Province, Thailand - Aung, Nang Kham; Ye, Yan (Scholar: Human Sciences, 2016)
The main purpose of this study was to determine the differences of teachers’ decision-making styles with their job satisfaction in four selected migrant high schools in Mae Sot district, Tak Province, Thailand. A total of one hundred and sixteen (116) teachers from the four schools were surveyed. The main source of the data was a set of questionnaires which investigated the teachers’ decision making styles and their job satisfaction levels. The collected data were analyzed by using the frequency, percentage, mean, standard deviation and one-way ANOVA. The study found that “Group Decision Making Style” was the most perceived decision making style used by the teachers in the four schools, and from the results of teachers’ satisfaction, it was found that their job satisfaction levels were regarded as ‘neither’. Therefore the hypothesis was accepted as the study discovered that there was a significance difference in teachers’ job satisfaction between teachers who preferred autocratic decision making style and teachers who preferred consultative decision making style among different decision making styles in the four selected migrant high schools in Mae Sot district, Tak Province, Thailand. Teachers are recommended to establish a teachers’ group to regularly meet and discuss openly all issues in their professional and personal lives which impact their decision-making and job satisfaction. They should be made aware of the impact these issues can have on their own performance and student achievement, Schools Leaders and Administrators should recognize the importance of decision-making and that it could affect the school’s success or failure. A workshop should be set up immediately for both teachers and leaders to get practical experience in making the best choice of decision making styles. Also weekly teacher development meetings should be arranged for all teachers to discuss and share ideas on job satisfaction issues, both intrinsic and extrinsic. Future researchers are recommended to conduct similar studies on other management issues in schools to improve teachers’ job satisfaction and the academic progress of students, e.g. student-based learning, student and teacher motivation, teacher incentives and rewards. These studies would be invaluable in improving the education system in Myanmar and to bring them in line with standards in firstly ASEAN member countries and worldwide.